2005
DOI: 10.1161/01.cir.0000160866.90148.76
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intensive Lipid Lowering, With or Without Antioxidant Vitamins, Compared With Moderate Lipid Lowering on Myocardial Ischemia in Patients With Stable Coronary Artery Disease

Abstract: Background-Lipid lowering with statins prevents adverse cardiac events. Both lipid-lowering and antioxidant therapies may favorably affect vasomotor function and thereby improve ischemia. Methods and Results-In a randomized, double-blind, placebo-controlled trial, 300 patients with stable coronary disease, a positive exercise treadmill test, 48-hour ambulatory ECG with Ն1 episode of ischemia, and fasting total cholesterol of 180 to 250 mg/dL were assigned to 1-year treatment with intensive atorvastatin to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…The reductions in ischemia from baseline in SAGE confirm the results from the Vascular Basis for the Treatment of Myocardial Ischemia study, which likewise revealed significant reductions in ischemia as measured by 48-hour ambulatory ECG in stable CAD patients randomized to an intensive (atorvastatin) or a moderate (lovastatin) statin regimen. 10 In SAGE, the change in total duration of myocardial ischemia was already evident at 3 months with no further improvement at month 12 and may indicate that reduction in coronary tone preceded changes in plaque composition, which are responsible for most cardiac events. In the Vascular Basis for the Treatment of Myocardial Ischemia study, it was hypothesized that there was a threshold effect of LDL-C lowering below which there is no incremental improvement in endothelial dysfunction and episodic coronary vasoconstriction, the mechanisms that contribute to the development of ischemia, and that the on-treatment LDL-C values in both groups in the Vascular Basis for the Treatment of Myocardial Ischemia study were beneath this threshold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reductions in ischemia from baseline in SAGE confirm the results from the Vascular Basis for the Treatment of Myocardial Ischemia study, which likewise revealed significant reductions in ischemia as measured by 48-hour ambulatory ECG in stable CAD patients randomized to an intensive (atorvastatin) or a moderate (lovastatin) statin regimen. 10 In SAGE, the change in total duration of myocardial ischemia was already evident at 3 months with no further improvement at month 12 and may indicate that reduction in coronary tone preceded changes in plaque composition, which are responsible for most cardiac events. In the Vascular Basis for the Treatment of Myocardial Ischemia study, it was hypothesized that there was a threshold effect of LDL-C lowering below which there is no incremental improvement in endothelial dysfunction and episodic coronary vasoconstriction, the mechanisms that contribute to the development of ischemia, and that the on-treatment LDL-C values in both groups in the Vascular Basis for the Treatment of Myocardial Ischemia study were beneath this threshold.…”
Section: Discussionmentioning
confidence: 99%
“…7 In patients with stable CAD, too, statin therapy was associated with reductions in ambulatory ischemia, as compared with placebo in a randomized pilot study 8 and in a nonrandomized database study. 9 The recent Vascular Basis for the Treatment of Myocardial Ischemia Study 10 further demonstrated that both intensive and more moderate lipid-lowering regimens reduced the duration of ischemia from baseline as measured by ambulatory ECG in patients with stable CAD. However, the mean age of the participants in these studies ranged from 56 to 67 years, participants were predominantly male, and none of the studies addressed the unique group of older patients with stable CAD-a population that is at highest risk of cardiac events and mortality.…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20][21] We excluded 2 potentially eligible trials that compared different intensities of statin therapy: 1 trial enrolled only patients with familial hypercholesterolemia 22 and 1 enrolled a wide variety of patients of whom the majority (54%) did not have coronary artery disease. included in our review.…”
Section: Study Selection and Evaluationmentioning
confidence: 99%
“…included in our review. [15][16][17][18][19][20][21] Of these trials, 2 enrolled patients after acute coronary syndromes and 5 enrolled patients with chronic coronary artery disease. The demographic characteristics of study participants were similar across the included trials.…”
Section: Study Selection and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation